THE UNIVERSAL SIGNIFICANCE OF THE PLOT CONCERNING ALL MANKIND (Scientific journal of the Fergana State University, 2025)
Examples of literary art with wandering plots, widespread among various peoples, as well as works that arose as a result of literary influence, are not only a unique historical source of their time, but also a vivid expression of the literary and aesthetic potential and spiritual and moral views of representatives of a certain people. The plot of the story about Yusuf is considered such a literary phenomenon that has spread all over the world. This problem is discussed in detail in the article.